2016
DOI: 10.1186/s40064-016-1852-y
|View full text |Cite
|
Sign up to set email alerts
|

A sutureless technique using cyanoacrylate adhesives when creating a stoma for extremely low birth weight infants

Abstract: PurposeIntestinal perforation and necrotizing enterocolitis (NEC) are neonatal intestinal emergencies that are especially common in premature infants. While prompt surgical intervention, including stoma creation, is often required, the optimal surgical treatment has been controversial because of the substantial risks related to the stoma creation and management. The use of a tissue adhesive may have some advantages over the use of sutures when creating an intestinal stoma in extremely low birth weight (ELBW) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…compounds have been used as complement to conventional sutures. There are studies that show that they are able to create syntheses with no suture in intestines since they do not cause tissue ischemia 6,7 .…”
Section: IImentioning
confidence: 99%
“…compounds have been used as complement to conventional sutures. There are studies that show that they are able to create syntheses with no suture in intestines since they do not cause tissue ischemia 6,7 .…”
Section: IImentioning
confidence: 99%
“…This adverse pregnancy outcome may be influenced by several conditions, such as heart disease, diabetes, hypertension, behavioral disorders, impaired cognitive function, psychological disorders, and a substantial risk of complications related to the stoma includes the esophagus, stomach, duodenum, ileum, colon, pleural cavity, ureters, urinary bladder, and kidney pelvis etc. [ 8 ], and usually incurs long-term financial burdens for households [ 9 , 10 ]. Furthermore, with the demographic change of increased life expectancy at birth in developing countries, children born with LBW can cause an increased economic burden and an increased disease burden [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study compared the reaction to the absorbable suture thread with laser application. This demonstrated that photodynamic therapy was not appropriate forreabsorbable materials, since it promoted slower absorption of the material, which, in turn, triggered foreign body reactions during the observation period [14]. In this study, no differences were observed regarding the use of nylon or cyanoacrylate in the inflammatory response, with recruitment of lymphocytes, neutrophils, presence of edema and hyperemia.…”
Section: Discussionmentioning
confidence: 60%
“…The study of tissue reaction has a direct contribution on the prediction of results. Planning, execution and adoption of precautionary measures are of great importance in surgical practice, in order to reduce inflammatory response, as is as the use of photodynamic therapy to modulate inflammation, promote analgesic effects and induce tissue repair [14].…”
Section: Discussionmentioning
confidence: 99%